Biomarkers in primary open angle glaucoma - Kokotas,H.; Kroupis, C.; Chiras,D.; Grigoriadou,M.; Lamnissou, K.; Petersen, MB; Kitsos,G. (Clin.Chem.Lab Med., 2012)
Glaucoma, a leading cause of blindness worldwide, is currently defined as a disturbance of the structural or functional integrity of the optic nerve that causes characteristic atrophic changes in the optic nerve, which may lead to specific visual field defects over time. This disturbance usually can be arrested or diminished by adequate lowering of intraocular pressure (IOP). Glaucoma can be divided roughly into two main categories, ' open angle ' and ' closed angle ' glaucoma.Open angle, chronic glaucoma tends to progress at a slower rate and patients may not notice loss of vision until the disease has progressed significantly. Primary open angle glaucoma(POAG) is described distinctly as a multifactorial optic neuropathy that is chronic and progressive with a characteristic acquired loss of optic nerve fibers. Such loss develops in the presence of open anterior chamber angles, characteristic visual field abnormalities, and IOP that is too high for the healthy eye. It manifests by cupping and atrophy of the optic disc, in the absence of other known causes of glaucomatous disease. Several biological markers have been implicated with the disease. The purpose of this study was to summarize the current knowledge regarding the non-genetic molecular markers which have been predicted to have an association with POAG but have not yet been validated
Keywords: analysis; Biomarkers; Diagnosis; Glaucoma,Open-Angle; Greece; Humans; Intraocular Pressure; physiopathology